PENGARUH KOMITMEN ORGANISASIONAL,KOMPENSASI DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARIAWAN PT.BPR KERINCI - Desi, Dona Elvia; Dosari , Nika (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Turnover intention is the tendency or intention of employees to voluntarily stop working from their jobs or move from one workplace to another according to their own choice (Mobley, 2011). Turnover intention does not stand alone, there are things that encourage the behavior of these employees. Someone will not leave the organization without a reason/factor that triggers the desire to move/turnover intention. Many factors affect Turnover intention including organizational commitment, compensation and job satisfaction (Mobley, 2011). This study aims to see the influence and magnitude of the influence of organizational commitment, compensation and job satisfaction on Turnover intention of PT. BPR Kerinci. By using validity and reliability tests on research instruments, the samples in this research were employees of PT. BPR Kerinci as many as 30 people. With multiple linear regression analysis tools, determinant coefficients and hypothesis testing with t test and F test it is obtained that partially organizational commitment and compensation have a negative and significant effect on turnover invention, while job satisfaction has no significant effect on Turnover intention . Simultaneously, organizational commitment, compensation and job satisfaction have a significant effect on turnover intention at PT. BPR Kerinci.